Dakwah Nabi Nuh ‘Alaihissalam: Studi Tafsir Tematik Dakwah Nabi Nuh dalam Surat Nuh - Qonita Nurshabrina (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
This study aims to examine the concept of da'wah carried out by the Prophet Noah AS which is enshrined in the sura>h Nu> h. In this study, the authors used library research by collecting the da'wah verses contained in the sura>h Nu> h} and then analyzing them by referring to the interpretation literature and books related to the research theme. In conclusion, there are at least four messages of the Prophet Nu> h} that are contained in sura>h Nu> h }, namely the command to worship and be devout to Allah SWT, to always do istighfar for all the sins that have been committed, to meditate on creation and the blessings that Allah has given, the last is to always pray for the goodness of others, especially parents.